Pengaruh Tekanan Eksternal, Pengendalian Internal, Ketidakpastian Lingkungan dan Komitmen Organisasi Pada Penerapan Transparansi Pelaporan Keuangan - Wintari, Komang Ayu Tri; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2018)
In the current era of regional autonomy, transparency regarding government financial management is essential. The community hopes that regional autonomy creates the efficiency and effectiveness of local resource management, and creates space for the people to participate in the development process. This study aims to obtain empirical evidence about the influence of external pressure, internal control, environmental uncertainty and organizational commitment on the implementation of transparency of financial reporting Organization of Regional Devices.   Data collection method in this research is the use of questionnaire survey.   Sample collection using Purposive sampling. The number of respondents who participated in the filling questionnaire were 90 respondents. The collected data is processed by using multiple linear regression analysis.   The results of this study indicate that external pressure, internal control, environmental uncertainty and organizational commitment have a significant positive effect on the transparency of financial reporting. Keywords: External pressure, internal control, environmental uncertainty, organizational commitment, transparency of financial reporting.